2003
DOI: 10.1016/s0269-7491(02)00234-8
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate statistical study of heavy metal enrichment in sediments of the Pearl River Estuary

Abstract: analysis identified the heavy metal accumulation layers of sediment profiles and showed the various sources of metals in the estuary. AbstractThe concentrations and chemical partitioning of heavy metals in the sediment cores of the Pearl River Estuary were studied. Based on Pearson correlation coefficients and principal component analysis results, Al was selected as the concentration normalizer for Pb, while Fe was used as the normalizing element for Co, Cu, Ni and Zn. In each profile, sections with metal conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
164
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(176 citation statements)
references
References 24 publications
(34 reference statements)
7
164
0
5
Order By: Relevance
“…Hence, great concern has arisen in recent years over environmental pollution in this coastal region. Elevated concentrations of Cu, Pb, and Zn in the sediments of the PRE have been found (Chen and Zhou, 1992;Zheng, 1992;Li et al, 2000aLi et al, , 2000bLi et al, and 2001Liu et al, 2003). Trace metal contamination of the PRE may have a significant impact on aquatic organisms, disturbing the area's delicate ecological balance and potentially contaminating the marine food chain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, great concern has arisen in recent years over environmental pollution in this coastal region. Elevated concentrations of Cu, Pb, and Zn in the sediments of the PRE have been found (Chen and Zhou, 1992;Zheng, 1992;Li et al, 2000aLi et al, , 2000bLi et al, and 2001Liu et al, 2003). Trace metal contamination of the PRE may have a significant impact on aquatic organisms, disturbing the area's delicate ecological balance and potentially contaminating the marine food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Stable Pb isotopic studies have been commonly applied to assess the sources of Pb in various ecosystems, including sediments (Farmer et al, 1996;Ritson et al, 1999;Liu et al, 2003), soils (Sugden et al, 1993;Semlali et al, 2001;Wong et al, 2002), suspended matters (Hinrichs et al, 2002), and atmospheric depositions Rosman, 2000 andWong et al, 2003). However, only a few studies have focused on stable Pb isotopes in biological samples to trace the anthropogenic origins of Pb (Kurkjian and Flegal, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Vertical profiles of trace elements and Mn in the sediments from the Pearl River and estuary the estuarine environment was seawater; the marine source of Na also showed a strong relationship with Mg and K (Spencer 2002). Previous studies in the Pearl River Estuary had also showed that the distribution of Mg and Ca may reflect the combined effects of parent material influences and sedimentation processes in the interaction with marine water (Li et al 2000;Liu et al 2003). Na had a strong positive correlation with Mg and a negative correlation with K in this study (Table 6).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The PRE has been a hot spot for research in recent decades (Li et al 2000;Liu et al 2003;Ip et al 2007;Zhou et al 2009;Yu et al 2010Yu et al , 2012. Because of the heavy metal toxicity to aquatic and benthonic organisms and the subsequent effects on humans, the geochemical behavior and pollution assessment of heavy metals account for a large fraction of these studies.…”
Section: Introductionmentioning
confidence: 99%